A soft magnetic composite material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611023959.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-09-01
AI Technical Summary
[0005]尽管上述现有技术在一定程度上改善了软磁复合材料的高频磁损耗特性,但仍存在诸多局限,具体表现为:磁损耗降低幅度有限,制备工艺流程繁琐,多层包覆结构的稳定性与均匀性难以精准把控,且原材料成本居高不下
[0078] This invention combines FeSiAl powder and FeNi powder, leveraging the complementary and synergistic effects of the two materials' mechanical and magnetic properties to improve magnetic permeability. Furthermore, by sieving and selecting FeSiAl and FeNi powders with appropriate particle sizes, it helps reduce eddy current losses within the particles and weaken the skin effect at high frequencies. By coating with a uniform, complete, and dense SiO2 insulating layer, it helps reduce eddy current losses between particles. The synergistic effect of these three factors enables the soft magnetic composite material to have both high magnetic permeability and extremely low high-frequency magnetic loss.
Smart Images

Figure CN122677296A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of soft magnetic materials technology, and relates to a soft magnetic composite material, and more particularly to a soft magnetic composite material and its preparation method and application. Background Technology
[0002] Soft magnetic materials have wide applications in numerous technological fields, including power electronics, and are commonly found in sensor measuring elements, transformer cores, motor cores, and inductors in switching power supplies. Research estimates suggest that the use of high-performance, advanced soft magnetic materials could potentially reduce global electricity consumption by 15% to 30%. Compared to traditional soft magnetic materials, soft magnetic composite materials exhibit superior permeability, lower magnetic losses, enhanced magnetic field stability, and higher DC bias performance. These characteristics not only improve energy conversion efficiency and enhance equipment reliability but also facilitate the miniaturization, high-frequency operation, and high-energy-density development of electronic devices, while minimizing unnecessary power losses.
[0003] However, while existing soft magnetic composite materials possess certain advantages in basic magnetic properties, they still struggle to achieve both extremely low magnetic loss and high permeability in practical high-frequency magnetic field environments. This is mainly due to two key factors: Firstly, the integrity, thickness uniformity, and insulation reliability of the insulating coating layer in existing soft magnetic composite materials are not effectively guaranteed. In high-frequency magnetic field environments, even minor defects or uneven thickness in the insulating coating layer can easily lead to electrical contact between magnetic powder particles, resulting in severe eddy current losses and significantly limiting the material's application performance in high-frequency magnetic field environments. Secondly, current technologies lack precise sieving and optimization of soft magnetic powder particle size. Appropriate soft magnetic powder core particle size can not only maintain relatively high permeability but also effectively suppress eddy current losses within the particles and significantly reduce the skin effect at high frequencies.
[0004] To optimize the quality of the coating layer and the matching of particle size, some related improvements have been attempted in the prior art. CN121964371A discloses a method for preparing soft magnetic composite powder, which constructs a multilayer coating of carbonyl iron powder with phosphoric acid, silane coupling agent, amorphous magnetic powder and resin. The magnetic powder after acid washing is introduced into the amorphous magnetic powder as a magnetic conductive layer, which can achieve high resistivity with almost no sacrifice of overall permeability. The resin coating can reduce eddy current loss under high frequency conditions and improve its DC bias capability while ensuring permeability. CN121748155A discloses a method for preparing a low-cost, high-performance nanocrystalline composite material. This process involves inorganically coating iron-based nanocrystalline powder, FeNi powder, and FeSiAl powder separately, then mixing them, followed by resin insulating coating. The SiO2 inorganic layer and the resin organic layer have high resistivity, and SiO2 is chemically stable. The double-layer coating significantly improves the particle coating efficiency. The Al2O3 inorganic layer and the resin organic layer also have high resistivity, and Al2O3 has high thermal conductivity. While ensuring good electrical insulation, the composite material's thermal conductivity and heat dissipation capabilities are significantly improved. CN118888241A discloses an iron-based multi-powder soft magnetic composite material and its preparation method. By rationally combining three types of magnetic powder with six particle sizes, the spacing between the magnetic powder particles is effectively adjusted. The addition of smaller particles increases the density of the magnetic powder core and, to some extent, reduces misalignment during subsequent pressing and annealing processes. This results in a more orderly arrangement of particles within the magnetic powder core, improving its performance and consequently its magnetic and mechanical properties.
[0005] Although the aforementioned existing technologies have improved the high-frequency magnetic loss characteristics of soft magnetic composite materials to some extent, they still have many limitations, namely: the reduction in magnetic loss is limited, the preparation process is complicated, the stability and uniformity of the multilayer coating structure are difficult to control precisely, and the cost of raw materials remains high.
[0006] Therefore, developing a simple preparation method that can significantly reduce high-frequency magnetic loss of soft magnetic composite materials while maintaining excellent high-frequency magnetic properties is an urgent problem to be solved in this field. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the present invention aims to provide a soft magnetic composite material, its preparation method, and its applications. This invention combines FeSiAl powder and FeNi powder, further sieves to select appropriate particle sizes, and coats them with a dense SiO2 insulating layer. The synergistic effect of these three components gives the soft magnetic composite material high magnetic permeability while also exhibiting extremely low high-frequency magnetic loss.
[0008] To achieve this objective, the present invention adopts the following technical solution:
[0009] In a first aspect, the present invention provides a method for preparing a soft magnetic composite material, comprising the following steps:
[0010] (1) FeSiAl powder with an average particle size of 15μm~20μm and FeNi powder with an average particle size of 8μm~10μm were obtained by sieving.
[0011] (2) Coat the FeSiAl powder and the FeNi powder with SiO2 insulating layer respectively to obtain SiO2-FeSiAl powder and SiO2-FeNi powder.
[0012] (3) The SiO2-FeNi powder and the SiO2-FeSiAl powder are mixed once to obtain a mixed powder.
[0013] (4) The binder solution and the mixed powder are mixed again, cured, pressed and annealed to obtain the soft magnetic composite material.
[0014] For example, in step (1), the average particle size of FeSiAl powder can be 15μm, 16μm, 17μm, 18μm, 19μm or 20μm, etc.; the average particle size of FeNi powder can be 8μm, 8.5μm, 9μm, 9.5μm or 10μm, etc.
[0015] It should be noted that in step (1), the FeSiAl powder and FeNi powder are sieved according to the GB / T 6003.3-1999 standard.
[0016] This invention combines FeSiAl powder and FeNi powder, leveraging the complementary and synergistic effects of the two materials' mechanical and magnetic properties to improve magnetic permeability. Furthermore, by sieving and selecting FeSiAl and FeNi powders with appropriate particle sizes, it helps reduce eddy current losses within the particles and weaken the skin effect at high frequencies. By coating with a uniform, complete, and dense SiO2 insulating layer, it helps reduce eddy current losses between particles. The synergistic effect of these three factors enables the soft magnetic composite material to have both high magnetic permeability and extremely low high-frequency magnetic loss.
[0017] Preferably, in step (3), the mass of the SiO2-FeNi powder is 30wt% to 50wt% of the mass of the mixed powder, for example, it can be 30wt%, 35wt%, 40wt%, 45wt% or 50wt%.
[0018] Preferably, the mass of the SiO2-FeSiAl powder is 50wt% to 70wt% of the mass of the mixed powder, for example, it can be 50wt%, 55wt%, 60wt%, 65wt% or 70wt%.
[0019] In this invention, by adjusting the mass ratio of SiO2-FeNi powder to SiO2-FeSiAl powder, it is beneficial to achieve a performance balance between magnetic permeability and magnetic loss. If the mass of SiO2-FeNi is too high, the magnetic loss of the soft magnetic composite material will be too high; if the mass of SiO2-FeNi is too low, the magnetic permeability of the soft magnetic composite material will be too low.
[0020] Preferably, in step (2), the FeSiAl powder is coated with a SiO2 insulating layer using a sol-gel method to obtain SiO2-FeSiAl powder, which includes the following steps: adding the FeSiAl powder to an ethanol solution, adding a silicon source, a coupling agent and a pH adjuster, and performing a first reaction to obtain the SiO2-FeSiAl powder.
[0021] Preferably, in step (2), the FeNi powder is coated with a SiO2 insulating layer using a sol-gel method to obtain SiO2-FeNi powder, which includes the following steps: adding the FeNi powder to an ethanol solution, adding a silicon source, a coupling agent and a pH adjuster, and carrying out a second reaction to obtain the SiO2-FeNi powder.
[0022] In this invention, by coating FeSiAl powder and FeNi powder with a SiO2 insulating layer using the sol-gel method, a uniform, complete and dense SiO2 insulating layer can be constructed on the powder surface with strong bonding force. This can effectively block leakage magnetic field and electrical contact under high-frequency magnetic field, and significantly enhance the insulation reliability and magnetic field stability of the material.
[0023] Preferably, the silicon source comprises tetraethyl orthosilicate.
[0024] Preferably, the mass-to-volume ratio of the FeSiAl powder to the silicon source is 10 g / mL to 50 g / mL, for example, it can be 10 g / mL, 20 g / mL, 30 g / mL, 40 g / mL or 50 g / mL.
[0025] Preferably, the mass-to-volume ratio of the FeNi powder to the silicon source is 10 g / mL to 50 g / mL, for example, it can be 10 g / mL, 20 g / mL, 30 g / mL, 40 g / mL or 50 g / mL.
[0026] In this invention, the thickness of the SiO2 insulating layer can be controlled by adjusting the amount of silicon source used.
[0027] Preferably, the coupling agent includes KH-550.
[0028] Preferably, the mass-to-volume ratio of the FeSiAl powder to the coupling agent is 10 g / mL to 50 g / mL, for example, it can be 10 g / mL, 20 g / mL, 30 g / mL, 40 g / mL or 50 g / mL.
[0029] Preferably, the mass-to-volume ratio of the FeNi powder to the coupling agent is 10 g / mL to 50 g / mL, for example, it can be 10 g / mL, 20 g / mL, 30 g / mL, 40 g / mL or 50 g / mL.
[0030] Preferably, the pH adjuster includes ammonia.
[0031] Preferably, the amount of pH adjuster added is such that the pH of the system is 10.5 to 11.5, for example, 10.5, 11 or 11.5.
[0032] In this invention, by adjusting the amount of coupling agent and the pH of the system, it is beneficial to ensure that the coupling agent fully covers the surface of FeSiAl powder and / or FeNi powder and promotes the formation of a uniform SiO2 insulating layer.
[0033] Preferably, the volume concentration of the ethanol solution is 70 vol% to 90 vol%, for example, it can be 70 vol%, 75 vol%, 80 vol%, 85 vol%, or 90 vol%.
[0034] Preferably, the first reaction and the second reaction are carried out independently under stirring conditions.
[0035] Preferably, the stirring speed is 300 rpm to 500 rpm, for example, it can be 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm.
[0036] Preferably, the temperatures of the first reaction and the second reaction are each independently between 40°C and 60°C, for example, 40°C, 45°C, 50°C, 55°C, or 60°C.
[0037] Preferably, the time for the first reaction and the second reaction is independently 1h to 5h, for example, 1h, 2h, 3h, 4h or 5h.
[0038] In this invention, the formation quality of the SiO2 insulating layer can be ensured by controlling the timing of the first and / or second reactions. If the time is too short, the density and integrity of the SiO2 insulating layer will be insufficient; if the time is too long, the SiO2 insulating layer will be loose, affecting its insulation performance.
[0039] Preferably, in the SiO2-FeSiAl powder, the average thickness of the SiO2 insulating layer is 10nm~15nm, for example, it can be 10nm, 11nm, 12nm, 13nm, 14nm or 15nm, etc.
[0040] Preferably, in the SiO2-FeNi powder, the average thickness of the SiO2 insulating layer is 8nm~12nm, for example, it can be 8nm, 9nm, 10nm, 11nm or 12nm, etc.
[0041] In this invention, by controlling the thickness of the SiO2 insulating layer, it is beneficial to achieve a good insulating coating effect without introducing too many non-magnetic phases that would excessively reduce the magnetic permeability. If the SiO2 insulating layer is too thin, it is difficult to form a dense coating layer, and the effect of reducing magnetic loss cannot be achieved; if the SiO2 insulating layer is too thick, too many non-magnetic phases will be introduced, causing a serious decrease in magnetic permeability.
[0042] Preferably, after the first reaction and / or the second reaction are completed, the obtained solid product is washed and dried.
[0043] Preferably, the washing includes washing with ethanol two or three times.
[0044] Preferably, the drying process includes placing the item in an oven and drying it at 60°C to 100°C for 1 to 5 hours.
[0045] For example, the drying temperature can be 60°C, 70°C, 80°C, 90°C or 100°C, etc.; the drying time can be 1h, 2h, 3h, 4h or 5h, etc.
[0046] Preferably, in step (4), the annealing temperature is 400℃~800℃, for example, it can be 400℃, 500℃, 550℃, 600℃, 650℃, 700℃ or 800℃, etc., preferably 500℃~600℃.
[0047] In this invention, the annealing temperature has a significant impact on the performance of the soft magnetic composite material. Within a suitable temperature range, residual stress generated during the pressing process can be effectively released, internal micro-defects can be reduced, and structural uniformity can be optimized, thereby improving magnetic permeability and reducing magnetic loss. Furthermore, under the specific process conditions of this invention, a suitable temperature can also promote the decomposition of the binder and facilitate the in-situ formation of a new coating layer composed of residual carbon and Al2O3 on the surface of the FeSiAl powder, resulting in a superior insulating coating effect and further enhancing insulation performance and DC bias characteristics.
[0048] Preferably, the holding time for the annealing treatment is 1h to 8h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0049] Preferably, the annealing treatment is carried out under an inert atmosphere, preferably a nitrogen atmosphere and / or an argon atmosphere.
[0050] Preferably, in step (1), the screening includes electromagnetic vibrating screening.
[0051] In this invention, compared with manual screening, electromagnetic vibration screening can achieve higher repeatability and less randomness in particle size distribution.
[0052] Preferably, the vibration amplitude of the electromagnetic vibrating screen is 1300r / min to 1500r / min, for example, it can be 1300r / min, 1350r / min, 1400r / min, 1450r / min or 1500r / min.
[0053] Preferably, the vibration interval of the electromagnetic vibrating screen is 3s to 10s, for example, it can be 3s, 5s, 8s or 10s.
[0054] Preferably, the total vibration time of the electromagnetic vibrating screen is 20 min to 60 min, for example, it can be 20 min, 30 min, 40 min, 50 min or 60 min.
[0055] Preferably, in step (3), the primary mixing includes ball milling.
[0056] Preferably, the ball milling and mixing is carried out using a horizontal ball mill.
[0057] Preferably, the mass ratio of balls in the ball mill mixture is 1 to 3, for example, it can be 1, 1.5, 2, 2.5 or 3, etc.
[0058] Preferably, the ball milling speed is 20Hz / min to 50Hz / min, for example, it can be 20Hz / min, 30Hz / min, 40Hz / min or 50Hz / min.
[0059] In this invention, the ball milling speed should be controlled between 20 Hz / min and 50 Hz / min. If the speed is too high, the mixed powder particles will break down, severely reducing the magnetic properties.
[0060] Preferably, the ball milling mixing time is 5h to 10h, for example, it can be 5h, 6h, 7h, 8h, 9h or 10h.
[0061] Preferably, in step (4), the adhesive of the adhesive solution includes epoxy resin.
[0062] Preferably, the solvent of the adhesive solution is an organic solvent, preferably acetone.
[0063] Preferably, the mass of the binder is 1.0wt% to 1.2wt% of the mass of the mixed powder, for example, it can be 1.0wt%, 1.1wt% or 1.2wt%.
[0064] Preferably, the temperature of the secondary mixing is 40℃~50℃, for example, it can be 40℃, 42℃, 45℃, 48℃ or 50℃, etc.
[0065] Preferably, the solvent in the secondary mixing of the binder solution is evaporated to dryness.
[0066] Preferably, the curing temperature is 90℃~110℃, for example, it can be 90℃, 95℃, 100℃, 105℃ or 110℃.
[0067] Preferably, the curing time is 1h to 3h, for example, it can be 1h, 1.5h, 2h, 2.5h or 3h.
[0068] Preferably, the pressing pressure is 1GPa to 2GPa, for example, it can be 1GPa, 1.2GPa, 1.5GPa, 1.8GPa or 2GPa.
[0069] Preferably, the method for preparing the soft magnetic composite material includes the following steps:
[0070] (1) Electromagnetic vibration sieving yields FeSiAl powder with an average particle size of 15μm~20μm and FeNi powder with an average particle size of 8μm~10μm. The vibration amplitude of the electromagnetic vibration sieving is 1300r / min~1500r / min, the vibration interval is 3s~10s, and the total vibration time is 20min~60min.
[0071] (2) The FeSiAl powder and the FeNi powder are coated with SiO2 insulating layers using the sol-gel method to obtain SiO2-FeSiAl powder and SiO2-FeNi powder, respectively. In the SiO2-FeSiAl powder, the average thickness of the SiO2 insulating layer is 10nm~15nm; in the SiO2-FeNi powder, the average thickness of the SiO2 insulating layer is 8nm~12nm.
[0072] (3) The SiO2-FeNi powder and the SiO2-FeSiAl powder are ball-milled to obtain a mixed powder. The mass of the SiO2-FeNi powder is 30wt%~50wt% of the mass of the mixed powder, and the mass of the SiO2-FeSiAl powder is 50wt%~70wt% of the mass of the mixed powder. The ball-to-powder mass ratio is 1~3, the rotation speed is 20Hz / min~50Hz / min, and the time is 5h~10h.
[0073] (4) The binder solution and the mixed powder are mixed twice at 40℃~50℃, the solvent in the binder solution is evaporated, cured at 90℃~110℃ for 1h~3h, pressed into shape under a pressure of 1GPa~2GPa, and annealed at 400℃~800℃ in an inert atmosphere for 1h~8h to obtain the soft magnetic composite material. The binder in the binder solution includes epoxy resin, and the solvent is an organic solvent; the mass of the binder is 1.0wt%~1.2wt% of the mass of the mixed powder.
[0074] In a second aspect, the present invention provides a soft magnetic composite material, which is prepared by the preparation method described in the first aspect.
[0075] Thirdly, the present invention provides an application of the soft magnetic composite material as described in the second aspect, wherein the soft magnetic composite material is used in electronic devices.
[0076] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0077] Compared with the prior art, the present invention has the following beneficial effects:
[0078] This invention combines FeSiAl powder and FeNi powder, leveraging the complementary and synergistic effects of the two materials' mechanical and magnetic properties to improve magnetic permeability. Furthermore, by sieving and selecting FeSiAl and FeNi powders with appropriate particle sizes, it helps reduce eddy current losses within the particles and weaken the skin effect at high frequencies. By coating with a uniform, complete, and dense SiO2 insulating layer, it helps reduce eddy current losses between particles. The synergistic effect of these three factors enables the soft magnetic composite material to have both high magnetic permeability and extremely low high-frequency magnetic loss. Attached Figure Description
[0079] Figure 1 This is a comparison chart of the effective magnetic permeability of the soft magnetic composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 2 of the present invention at different frequencies.
[0080] Figure 2 This is a comparison chart of the effective magnetic permeability of the soft magnetic composite materials obtained in Examples 10-15 and Comparative Examples 2-3 of the present invention at different frequencies.
[0081] Figure 3These are comparison diagrams of the core losses of the soft magnetic composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 2 of the present invention under an external magnetic field of 10mT and frequencies of 1000kHz to 3000kHz.
[0082] Figure 4 This is a comparison diagram of the core loss of the soft magnetic composite materials obtained in Examples 10 to 15 and Comparative Examples 2 to 3 of the present invention under an external magnetic field of 10mT and a frequency of 1000kHz to 3000kHz.
[0083] Figure 5 These are comparison diagrams of the core loss of the soft magnetic composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 2 of the present invention under an applied magnetic field of 50mT and a frequency of 50kHz to 500kHz.
[0084] Figure 6 These are comparison diagrams of the core loss of the soft magnetic composite materials obtained in Examples 10 to 15 and Comparative Examples 2 to 3 of the present invention under an applied magnetic field of 50 mT and a frequency of 50 kHz to 500 kHz. Detailed Implementation
[0085] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0086] The scope of this invention can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form an effective range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this invention. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this invention. In this invention, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0087] Unless otherwise specified, the term "at least two combinations" in this invention refers to a quantity greater than or equal to 2. For example, "any one or at least two combinations" means that any one of the listed items can be selected, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this invention.
[0088] In this invention, unless otherwise specified, the feature or solution corresponding to "and / or" covers any one of two or more related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a set consisting of A, B, and combinations of A and B. "Including A and / or B" can be understood, depending on the context of the statement, as including A, including B, or simultaneously including both A and B. In this invention, "optional" means that the corresponding feature, component, step, or solution is not essential, i.e., selected from either "present" or "absent" parallel solutions. If multiple "optional" limitations appear in a technical solution, unless otherwise specified and without technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.
[0089] In this invention, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond the listed elements unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A may consist only of a1, a2, and a3, or it may include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements."
[0090] All embodiments and optional embodiments of the present invention, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of the present invention. The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment can be included in at least one embodiment or implementation of the present invention. The appearance of this phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in this invention can be combined with other embodiments without technical conflict.
[0091] In this invention, the ordinal numbers “first,” “second,” “third,” and “fourth” used in expressions such as “first aspect,” “second aspect,” “third aspect,” and “fourth aspect” are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.
[0092] In this invention, the order in which the steps are written in the methods described in each embodiment does not imply a strict execution order. The actual execution order of each step should be determined based on its function and possible internal logic. Unless otherwise specified, all steps of this invention can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.
[0093] Example 1
[0094] This embodiment provides a method for preparing a soft magnetic composite material, including the following steps:
[0095] (1) Electromagnetic vibration sieving yielded FeSiAl powder with an average particle size of 15 μm and FeNi powder with an average particle size of 10 μm.
[0096] The electromagnetic vibrating screen has a vibration amplitude of 1400 r / min, a vibration interval of 5 s, and a total vibration time of 30 min. The screens selected are 700 mesh and 1250 mesh screens that conform to the GB / T 6003.3-1999 standard.
[0097] (2) Place 40g of FeSiAl powder into a 250ml beaker, add 30mL of deionized water and 170mL of anhydrous ethanol, fix the beaker in a constant temperature water bath, set the temperature of the constant temperature water bath to 50℃, then fix the electric stir head at a position 5mm away from the bottom of the beaker, stir for 3min to form a uniform suspension, add 1mL of coupling agent and stir for 10min, add 1.5mL of ammonia water to adjust the pH to 11 and stir for 2min, add 2mL of tetraethyl orthosilicate, cover the beaker with plastic wrap and stir for 3h. After the reaction is complete, wash the obtained solid product three times with anhydrous ethanol, and then put it in an oven to dry at 80℃ for 2h to obtain SiO2-FeSiAl powder.
[0098] In the SiO2-FeSiAl powder, the average thickness of the SiO2 insulating layer is 12 nm.
[0099] (3) Place 40g of FeNi powder into a 250ml beaker, add 30mL of deionized water and 170mL of anhydrous ethanol, fix the beaker in a constant temperature water bath, set the temperature of the constant temperature water bath to 50℃, then fix the electric stir head at a position 5mm away from the bottom of the beaker, stir for 3min to form a uniform suspension, add 1mL of coupling agent and stir for 10min, add 1.5mL of ammonia water to adjust the pH to 11 and stir for 2min, add 2mL of tetraethyl orthosilicate, cover the beaker with plastic wrap and stir for 3h. After the reaction is complete, wash the obtained solid product three times with anhydrous ethanol, and then put it in an oven to dry at 80℃ for 2h to obtain SiO2-FeNi powder.
[0100] In the SiO2-FeNi powder, the average thickness of the SiO2 insulating layer is 10 nm.
[0101] (4) Add 15g of SiO2-FeNi powder and 35g of SiO2-FeSiAl powder (mass ratio of 3:7) into a ball mill jar, then add a mixture of balls with a mass ratio of 1.5, place the ball mill jar on a horizontal ball mill, and ball mill the mixture at a speed of 50Hz / min for 5h to obtain the mixed powder.
[0102] (5) Place 50g of mixed powder into a 100ml beaker, add 0.6g of epoxy resin (1.2wt% of the mass of the mixed powder), add 10mL of acetone, and stir with ultrasonic assistance at 50℃ until the acetone is completely evaporated; then place it in a vacuum drying oven and cure at 100℃ for 1.5h. Press the cured powder into shape, with a pressing pressure of 1.58GPa and a holding time of 1min; finally, anneal at 500℃ for 2h under an argon atmosphere to obtain a soft magnetic composite material.
[0103] Example 2
[0104] This embodiment provides a method for preparing a soft magnetic composite material. Except that the mass of SiO2-FeNi powder and SiO2-FeSiAl powder in step (4) is 25g and 25g respectively, that is, the mass ratio of the two is 5:5, the rest is the same as in Example 1.
[0105] Example 3
[0106] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 600°C, the rest is the same as in Example 1.
[0107] Example 4
[0108] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 600°C, the rest is the same as in embodiment 2.
[0109] Example 5
[0110] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 700°C, the rest is the same as in Example 1.
[0111] Example 6
[0112] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 700°C, the rest is the same as in embodiment 2.
[0113] Example 7
[0114] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 400°C, the rest is the same as in Example 1.
[0115] Example 8
[0116] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 400°C, the rest is the same as in embodiment 2.
[0117] Example 9
[0118] This embodiment provides a method for preparing a soft magnetic composite material. Except that the mass of SiO2-FeNi powder and SiO2-FeSiAl powder in step (4) is 35g and 15g respectively, that is, the mass ratio of the two is 7:3, the rest is the same as in Example 1.
[0119] Example 10
[0120] This embodiment provides a method for preparing a soft magnetic composite material, including the following steps:
[0121] (1) Electromagnetic vibration sieving yielded FeSiAl powder with an average particle size of 20 μm and FeNi powder with an average particle size of 8 μm.
[0122] The electromagnetic vibrating screen has a vibration amplitude of 1400 r / min, a vibration interval of 10 s, and a total vibration time of 20 min. The screens selected are 600 mesh and 1600 mesh screens that conform to the GB / T 6003.3-1999 standard.
[0123] (2) Place 40g of FeSiAl powder into a 250ml beaker, add 30mL of deionized water and 170mL of anhydrous ethanol, fix the beaker in a constant temperature water bath, set the temperature of the constant temperature water bath to 40℃, then fix the electric stir head at a position 5mm away from the bottom of the beaker, stir for 3min to form a uniform suspension, add 2mL of coupling agent and stir for 20min, add 1.5mL of ammonia water to adjust the pH to 11 and stir for 2min, add 1mL of tetraethyl orthosilicate, cover the beaker with plastic wrap and stir for 5h. After the reaction is complete, wash the obtained solid product three times with anhydrous ethanol, and then put it in an oven to dry at 80℃ for 2h to obtain SiO2-FeSiAl powder.
[0124] In the SiO2-FeSiAl powder, the thickness of the SiO2 insulating layer is 10 nm.
[0125] (3) Place 40g of FeNi powder into a 250ml beaker, add 30mL of deionized water and 170mL of anhydrous ethanol, fix the beaker in a constant temperature water bath, set the temperature of the constant temperature water bath to 60℃, then fix the electric stirrer at a position 5mm away from the bottom of the beaker, stir for 3min to form a uniform suspension, add 2mL of coupling agent and stir for 20min, add 1.5mL of ammonia water to adjust the pH to 11 and stir for 2min, add 1mL of tetraethyl orthosilicate, cover the beaker with plastic wrap and stir for 1h. After the reaction is complete, wash the obtained solid product three times with anhydrous ethanol, and then put it in an oven to dry at 80℃ for 2h to obtain SiO2-FeNi powder.
[0126] In the SiO2-FeNi powder, the thickness of the SiO2 insulating layer is 8 nm.
[0127] (4) Add 15g of SiO2-FeNi powder and 35g of SiO2-FeSiAl powder (mass ratio of 3:7) into a ball mill jar, then add a mixture of balls with a mass ratio of 3, place the ball mill jar on a horizontal ball mill, and ball mill the mixture at a speed of 20Hz / min for 10h to obtain the mixed powder.
[0128] (5) Place 50g of mixed powder into a 100ml beaker, add 0.5g of epoxy resin (1.0wt% of the mass of mixed powder), add 10mL of acetone, and stir with ultrasonic assistance at 40℃ until the acetone is completely evaporated; then place it in a vacuum drying oven and cure at 90℃ for 3h. Press the cured powder into shape, with a pressing pressure of 1GPa and a holding time of 3min; finally, anneal at 500℃ for 2h under an argon atmosphere to obtain a soft magnetic composite material.
[0129] Example 11
[0130] This embodiment provides a method for preparing a soft magnetic composite material. Except that the mass of SiO2-FeNi powder and SiO2-FeSiAl powder in step (4) is 25g and 25g respectively, that is, the mass ratio of the two is 5:5, the rest is the same as in Example 10.
[0131] Example 12
[0132] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 600°C, the rest is the same as in Example 10.
[0133] Example 13
[0134] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 600°C, the rest is the same as in Example 11.
[0135] Example 14
[0136] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 700°C, the rest is the same as in Example 10.
[0137] Example 15
[0138] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 700°C, the rest is the same as in Example 11.
[0139] Example 16
[0140] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 400°C, the rest is the same as in Example 10.
[0141] Example 17
[0142] This embodiment provides a method for preparing a soft magnetic composite material. Except for adjusting the annealing temperature in step (5) to 400°C, the rest is the same as in Example 11.
[0143] Example 18
[0144] This embodiment provides a method for preparing a soft magnetic composite material. Except that the mass of SiO2-FeNi powder and SiO2-FeSiAl powder in step (4) is 35g and 15g respectively, that is, the mass ratio of the two is 7:3, the rest is the same as in Example 10.
[0145] Comparative Example 1
[0146] This comparative example provides a method for preparing a soft magnetic composite material. Except for step (4), in which SiO2-FeNi powder is not added and the mass of SiO2-FeSiAl powder is adjusted to 50g (the total mass of SiO2-FeNi powder and SiO2-FeSiAl powder), the rest is the same as in Example 1.
[0147] Comparative Example 2
[0148] This comparative example provides a method for preparing a soft magnetic composite material. Except for step (4), in which SiO2-FeSiAl powder is not added and the mass of SiO2-FeNi powder is adjusted to 50g (the total mass of SiO2-FeNi powder and SiO2-FeSiAl powder), the rest is the same as in Example 1.
[0149] Comparative Example 3
[0150] This comparative example provides a method for preparing a soft magnetic composite material. Except for omitting steps (2) and (3) and directly adding equal masses of FeSiAl powder and FeNi powder in step (4), the rest is the same as in Example 1.
[0151] Comparative Example 4
[0152] This comparative example provides a method for preparing a soft magnetic composite material. Except for adjusting the average particle size of the FeSiAl powder to 10 μm, the rest is the same as in Example 1.
[0153] Comparative Example 5
[0154] This comparative example provides a method for preparing a soft magnetic composite material. Except for adjusting the average particle size of FeSiAl powder to 10 μm and the average particle size of FeNi powder to 15 μm, the rest is the same as in Example 1.
[0155] The effective permeability of the soft magnetic composite materials obtained in Examples 1 to 18 and Comparative Examples 1 to 5 was tested at frequencies ranging from 50 kHz to 2000 kHz, and the average effective permeability was calculated.
[0156] The core loss of the soft magnetic composite materials obtained in Examples 1 to 18 and Comparative Examples 1 to 5 was tested under external magnetic fields of 10mT, 50mT and 100mT and frequencies of 50kHz to 3MHz.
[0157] The test results are shown in Table 1 and Figures 1-6 As shown.
[0158]
[0159] Figure 1 This is a comparison chart of the effective magnetic permeability of the soft magnetic composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 2 at different frequencies; Figure 2 This is a comparison chart of the effective permeability of the soft magnetic composite materials obtained in Examples 10-15 and Comparative Examples 2-3 at different frequencies. It can be seen that the mixing ratio and annealing temperature significantly affect the magnitude and stability of the permeability of the soft magnetic composite materials. Excessively high annealing temperatures, such as in Examples 6 and 15, lead to a breakdown in permeability stability; unsuitable mixing ratios, such as in Comparative Example 2, also result in poor permeability stability; appropriate annealing temperature and suitable mixing ratios can achieve stable and relatively high permeability.
[0160] Figure 3 The graph shows a comparison of the core loss of the soft magnetic composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 2 under an applied magnetic field of 10 mT and a frequency of 1000 kHz to 3000 kHz. Figure 4This is a comparison of the core losses of the soft magnetic composite materials obtained in Examples 10-15 and Comparative Examples 2-3 at frequencies ranging from 1000kHz to 3000kHz under an applied magnetic field of 10mT. It can be seen that a suitable mixing ratio and appropriate annealing temperature have a significant effect on reducing high-frequency core losses. Examples 3, 4, 12, and 13 each have the lowest core loss values within their respective groups. This is because a suitable mixing ratio results in a uniform molded powder core structure, optimizes the air gap distribution, and an appropriate annealing temperature causes a beneficial transformation in the cladding layer structure, improving insulation performance and reducing core losses.
[0161] Figure 5 The graph shows a comparison of the core loss of the soft magnetic composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 2 under an applied magnetic field of 50mT and a frequency of 50kHz to 500kHz. Figure 6 These are comparison graphs showing the core losses of the soft magnetic composite materials obtained in Examples 10-15 and Comparative Examples 2-3 under an applied magnetic field of 50 mT and frequencies ranging from 50 kHz to 500 kHz. It can be seen that the core loss performance under low-frequency, high-magnetic-field conditions is basically consistent with that under high-frequency, low-magnetic-field conditions, fully demonstrating the importance of a suitable mixing ratio and appropriate annealing temperature for the core loss performance of the material.
[0162] Examples 1-8 and Examples 10-17 investigated the effects of annealing temperature on the permeability and core loss of soft magnetic composite materials. As shown in Table 1, the performance of permeability and core loss is poor when the temperature is too low, while excessively high temperature leads to large fluctuations in permeability and a surge in core loss.
[0163] In Examples 9 and 18, the mass ratio of SiO2-FeNi powder to SiO2-FeSiAl powder was adjusted so that the mass of SiO2-FeNi powder was outside the range of 30wt% to 50wt% of the mixed powder mass. This resulted in either excessively low magnetic permeability or excessively high core loss.
[0164] Comparative Examples 1 and 2 each contain only one of SiO2-FeSiAl powder and SiO2-FeNi powder, respectively. They cannot construct a mixed powder system with two components, and cannot overcome the performance shortcomings of single magnetic powder. While the core loss is significantly reduced, the permeability does not increase significantly.
[0165] In Comparative Example 3, since neither the FeSiAl nor FeNi powders were coated with a SiO2 insulating layer, the core loss decreased significantly, and the permeability even decreased. This indicates that relying solely on the residual carbon formed by the pyrolysis of epoxy resin and the new coating layer formed by Al2O3 has limitations in reducing core loss.
[0166] Comparative Examples 4 and 5 investigated the effects of the particle size and its relationship between FeSiAl and FeNi powders on the permeability and core loss of soft magnetic composite materials. It can be seen that an appropriate particle size is crucial for the overall performance of soft magnetic composite materials. Excessively large particle sizes make it difficult to produce a uniform powder core structure and hinder uniform coating during the coating stage, while excessively small particle sizes lead to severe deterioration of permeability. A suitable particle size ratio can produce a uniformly distributed powder core structure and optimize the air gap distribution.
[0167] In summary, this invention improves magnetic permeability by combining FeSiAl and FeNi powders, leveraging the complementary and synergistic effects of their mechanical and magnetic properties. Furthermore, selecting FeSiAl and FeNi powders with appropriate particle sizes through sieving helps reduce eddy current losses within the particles and weaken the skin effect at high frequencies. The uniform, complete, and dense SiO2 insulating layer further reduces eddy current losses between particles. The synergistic effect of these three factors results in a soft magnetic composite material with both high magnetic permeability and extremely low high-frequency magnetic loss.
[0168] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a soft magnetic composite material, characterized in that, Includes the following steps: (1) FeSiAl powder with an average particle size of 15μm~20μm and FeNi powder with an average particle size of 8μm~10μm were obtained by sieving; (2) Coating the FeSiAl powder and the FeNi powder with a SiO2 insulating layer respectively to obtain SiO2-FeSiAl powder and SiO2-FeNi powder; (3) The SiO2-FeNi powder and the SiO2-FeSiAl powder are mixed once to obtain a mixed powder; (4) The binder solution and the mixed powder are mixed again, cured, pressed and annealed to obtain the soft magnetic composite material.
2. The preparation method according to claim 1, characterized in that, In step (3), the mass of the SiO2-FeNi powder is 30wt%~50wt% of the mass of the mixed powder; Preferably, the mass of the SiO2-FeSiAl powder is 50wt% to 70wt% of the mass of the mixed powder.
3. The preparation method according to claim 1 or 2, characterized in that, In step (2), the FeSiAl powder is coated with a SiO2 insulating layer using the sol-gel method to obtain SiO2-FeSiAl powder, which includes the following steps: adding the FeSiAl powder to an ethanol solution, adding a silicon source, a coupling agent and a pH adjuster, and carrying out a first reaction to obtain the SiO2-FeSiAl powder; Preferably, the FeNi powder is coated with a SiO2 insulating layer using a sol-gel method to obtain SiO2-FeNi powder, comprising the following steps: adding the FeNi powder to an ethanol solution, adding a silicon source, a coupling agent and a pH adjuster, and carrying out a second reaction to obtain the SiO2-FeNi powder; Preferably, the silicon source comprises tetraethyl orthosilicate; Preferably, the mass-to-volume ratio of the FeSiAl powder to the silicon source is 10 g / mL to 50 g / mL; Preferably, the mass-to-volume ratio of the FeNi powder to the silicon source is 10 g / mL to 50 g / mL; Preferably, the coupling agent comprises KH-550; Preferably, the mass-to-volume ratio of the FeSiAl powder to the coupling agent is 10 g / mL to 50 g / mL; Preferably, the mass-to-volume ratio of the FeNi powder to the coupling agent is 10 g / mL to 50 g / mL; Preferably, the pH adjuster includes ammonia. Preferably, the amount of pH adjuster added is such that the pH of the system is 10.5 to 11.5; Preferably, the volume concentration of the ethanol solution is 70 vol% to 90 vol%. Preferably, the first reaction and the second reaction are carried out independently under stirring conditions; Preferably, the stirring speed is 300 rpm to 500 rpm; Preferably, the temperatures of the first reaction and the second reaction are each independently between 40°C and 60°C; Preferably, the time for the first reaction and the second reaction is each 1h to 5h independently; Preferably, in the SiO2-FeSiAl powder, the average thickness of the SiO2 insulating layer is 10 nm to 15 nm; Preferably, in the SiO2-FeNi powder, the average thickness of the SiO2 insulating layer is 8nm~12nm.
4. The preparation method according to any one of claims 1 to 3, characterized in that, In step (4), the annealing temperature is 400℃~800℃, preferably 500℃~600℃; Preferably, the holding time for the annealing treatment is 1 hour to 8 hours; Preferably, the annealing treatment is carried out under an inert atmosphere, preferably a nitrogen atmosphere and / or an argon atmosphere.
5. The preparation method according to any one of claims 1 to 4, characterized in that, In step (1), the screening includes electromagnetic vibrating screening; Preferably, the vibration amplitude of the electromagnetic vibrating screen is 1300 r / min to 1500 r / min; Preferably, the vibration interval of the electromagnetic vibrating screen is 3s to 10s; Preferably, the total vibration time of the electromagnetic vibrating screen is 20 min to 60 min.
6. The preparation method according to any one of claims 1 to 5, characterized in that, In step (3), the primary mixing includes ball milling mixing; Preferably, the mass ratio of balls to material in the ball milling mixture is 1 to 3; Preferably, the ball milling speed is 20Hz / min to 50Hz / min; Preferably, the ball milling mixing time is 5h to 10h.
7. The preparation method according to any one of claims 1 to 6, characterized in that, In step (4), the adhesive of the adhesive solution includes epoxy resin; Preferably, the solvent of the adhesive solution is an organic solvent, preferably acetone; Preferably, the mass of the binder is 1.0 wt% to 1.2 wt% of the mass of the mixed powder; Preferably, the temperature of the secondary mixing is 40℃~50℃; Preferably, the solvent in the secondary mixing of the adhesive solution is evaporated to dryness; Preferably, the curing temperature is 90℃~110℃; Preferably, the curing time is 1 hour to 3 hours; Preferably, the pressing pressure is 1 GPa to 2 GPa.
8. The preparation method according to claim 1, characterized in that, Includes the following steps: (1) Electromagnetic vibration sieving yielded FeSiAl powder with an average particle size of 15μm~20μm and FeNi powder with an average particle size of 8μm~10μm; The vibration amplitude of the electromagnetic vibrating screen is 1300 r / min to 1500 r / min, the vibration interval is 3 s to 10 s, and the total vibration time is 20 min to 60 min. (2) The FeSiAl powder and the FeNi powder were coated with SiO2 insulating layer by sol-gel method to obtain SiO2-FeSiAl powder and SiO2-FeNi powder respectively; In the SiO2-FeSiAl powder, the average thickness of the SiO2 insulating layer is 10nm~15nm; in the SiO2-FeNi powder, the average thickness of the SiO2 insulating layer is 8nm~12nm. (3) The SiO2-FeNi powder and the SiO2-FeSiAl powder are ball-milled and mixed to obtain a mixed powder; The mass of the SiO2-FeNi powder is 30wt%~50wt% of the mass of the mixed powder, and the mass of the SiO2-FeSiAl powder is 50wt%~70wt% of the mass of the mixed powder; the ball-to-material mass ratio of the ball milling mixture is 1~3, the rotation speed is 20Hz / min~50Hz / min, and the time is 5h~10h; (4) The binder solution and the mixed powder are mixed twice at 40℃~50℃. The solvent in the binder solution is evaporated, cured at 90℃~110℃ for 1h~3h, pressed and shaped under a pressure of 1GPa~2GPa, and annealed at 400℃~800℃ in an inert atmosphere for 1h~8h to obtain the soft magnetic composite material. The binder in the binder solution includes epoxy resin, and the solvent is an organic solvent; the mass of the binder is 1.0wt% to 1.2wt% of the mass of the mixed powder.
9. A soft magnetic composite material, characterized in that, The soft magnetic composite material is prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the soft magnetic composite material as described in claim 9, characterized in that, The soft magnetic composite material is used in electronic devices.
Citation Information
Patent Citations
Iron-based multi-powder soft magnetic composite material and preparation method thereof
CN118888241A
Preparation method of low-cost high-performance nanocrystalline composite material
CN121748155A
Preparation method of soft magnetic composite powder
CN121964371A